Intense 18F-FDG Uptake in Chronic Subcutaneous Opioid Injection Sites. (October 2016) - Salas Fragomeni, Roberto Andres; Rowe, Steven P.
Abstract : Abstract: Subcutaneous 18 F-FDG uptake is a common finding on PET scans, with causes including both benign and malignant conditions. Often, the pattern of uptake or the clinical indication for the PET scan will suggest the etiology. However, unusual or unexpected patterns may require careful clinical history. We report the case of a 45-year-old woman who underwent a PET/CT study for paraneoplastic syndrome evaluation and was found to have intense, extensive, bilaterally symmetric, nodular subcutaneous FDG uptake in the lower back and buttocks that was related to long-term repeated subcutaneous opioid injections.